Monitoring of daily training load and training load responses in endurance sports: What do coaches want? - Roos, L.; Taube, W.; Brandt, M.; Heyer, L.; Wyss, T. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2013)
Accurate assessment of training load (TL) and training load responses (TLR) might be useful for an optimized training regulation and prevention of overtraining. No consensus on a gold-standard for measuring TL or intensity in endurance sports has been reported in the available literature so far. The aim of the present article is i) to identify feasible parameters to measure TL and TLR in daily training and ii) to compare these scientific approaches with the needs of elite endurance coaches. Therefore, the first part provides a systematic review of the current literature and the second part concentrates on the results of a questionnaire that assessed the coaches` requirements for monitoring daily endurance training. The systematic review revealed that the combination of both quantitative and qualitative data seems most promising to evaluate TL and TLR. Thus, validated questionnaires or rating of perceived exertion (RPE), combined with physiological parameters, such as heart rate, are often used and seem to provide the most reliable results. From the coaches` perspective, duration and kind of training, RPE, as well as personal remarks in the athletes` training diaries are considered to be essential information. Further, the coaches favor a feasible system that collects large amounts of directly measurable and perceived data and that is able to learn from previous events in order to present the most important information in a short individual overview. When comparing both parts of the present study, it becomes clear that the scientific research cannot yet fully respond to the coaches` requests, however, based on the coaches` propositions, scientific research might be stimulated to tackle this challenge in the near future.